The Circadian Clock - Albrecht, Urs.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This comprehensive book, written by experts in the field, provides historical and current information about the circadian clock, molecular properties of clock components and their roles in health and disease. The Circadian Clock includes advances in several aspects of clock research with chapters ranging from gene expression, mathematical modeling, physiology, neuroscience and comparitive biology. It aims to give an integrated view how the biochemistry and physiology of an organism is organized over the 24 hours of a day and how disturbance of clock function can lead to disease. The Circadian Clock is an ideal book for researchers, clinicians and graduate students in the fields of biochemistry, cell biology, physiology, neuroscience and bioinformatics.
A History of Chronobiological Concepts -- Transcriptional Regulation of Circadian Clocks -- Posttranslational Regulation of Circadian Clocks -- Nonimage Forming Photoreceptors -- Circadian Clocks and Metabolism -- Circadian Clock, Cell Cycle and Cancer -- Comparative Clocks -- Circadian Neural Networks -- The Circadian Clock and the Homeostatic Hourglass: Two Timepieces Controlling Sleep and Wakefulness -- Clocks, Brain Function, and Dysfunction -- Systems Biology and Modeling of Circadian Rhythms.
Keywords: Life sciences; Human physiology; Biochemistry; Cytology; Neurobiology; Life Sciences; Biochemistry, general; Animal Biochemistry; Medical Biochemistry; Cell Biology; Human Physiology; Neurobiology